Implementasi Sistem Pengukuran Redaman Serat Optik Pada Lekukan - Lince Markis -; Vera Veronica -; Uzma Septima - (Jurnal Ilmiah Poli Rekayasa, 2019)
Dutch electronics company, Philips, is testing LiFi technology. LiFi or Light Fidelity is able to deliver broadband internet connections through light intermediaries. According to Philips Lightning Olivia Qiu's Chief Innovation Officer, LiFi technology has great potential for today's digital era. Indeed, if you look at the current world trend, internet connection has now become one of the daily needs of humans just like the lighting needs produced by Philips massively. When radio frequency becomes increasingly dense, the light spectrum is a large untapped resource [kompas, 2018]. Based on the facts stated that communication using optical fiber becomes very important so that to optimize the fiber optic system an implementation of optical fiber attenuation measurements is made. In this study, the method of implementing the measurement of optical fiber attenuation at a wavelength of 875 nm was introduced. This optical fiber attenuation measurement utilizes transmitter and receiver optical fiber systems that are connected to optical fibers with different lengths and curves. Attenuation for the length of 1, 3, 4, 5 and 6 meter optical fibers is 0.034, 0.558, 0.625, 1.156 and 2.170 dB respectively in straight optical fiber conditions. The power values for each optical fiber with lengths 1, 3,4,5 and 6m respectively are 52.21, 51.58, 50.81, 45.08 and 30.05 dB when there are curves. The attenuation values of each 1, 3, 4, 5 and 6 m optical fiber lengths are - 0.746, - 0.8, - 0.864, - 1,384 and - 3,145 dB respectively when there is a curve.